Localized Green Fabrication of Hydroxyapatite/ZnO Nanocomposite: Toward A Sustainable Antibacterial Biomaterial - Arie Hardian; Farah Nur Fauziyah; Teguh Karya; Dani Gustaman Syarif; Atiek Rostika Noviyanti; Jasmansyah Jasmansyah; Muhammad Reza; Anceu Murniati; Kiki Adi Kurnia; Yanuar Setiadi; Ismunandar Ismunandar (Directorate for Research and Innovation (DRI) ITB, 2026)
Using a plant-assisted sol–gel strategy, a hydroxyapatite–zinc oxide (HAp/ZnO) composite was produced from Padalarang calcite and lemon (Citrus limon L.) extract. The calcite supplied the calcium component, while constituents of the lemon extract promoted metal-ion complexation and helped control precursor stabilization. This environmentally friendly approach reduces the use of hazardous chemicals while facilitating the formation and stabilization of the composite precursor during the sol–gel process. The synthesized HAp/ZnO nanocomposite exhibited crystalline HAp and ZnO phases and the mean crystallite dimension calculated from the diffraction data was 45.52 nm. XRF analysis confirmed the elemental composition and Ca/P ratio, while FTIR spectroscopy identified the characteristic functional groups of HAp and ZnO. Further, SEM observations revealed the particle morphology of the nanocomposite. In disk-diffusion testing against Escherichia coli, the inhibition diameter increased from 5 mm at 5 mg/mL to 15 mm at 20 mg/mL. The antibacterial response was interpreted mainly in terms of ZnO-derived reactive oxygen species and the action of released Zn2+ ions. The findings of this study indicate that the synthesized HAp/ZnO nanocomposite is a promising candidate material for further investigation in the development of sustainable antibacterial biomaterials.